Mediating effects of psychological safety in the relationship between team affectivity and transactive memory systems. (2nd September 2015) - Hood, Anthony C.; Bachrach, Daniel G.; Zivnuska, Suzanne; Bendoly, Elliot
Summary: In this research, we develop a framework for understanding the emergence of transactive memory systems (TMS) in project‐based teams characterized by different levels of group level positive affectivity (PA) and negative affectivity (NA). With a focus on enhancing understanding of the means of transmission, we test the mediating role played by group level psychological safety (PS) in the relationship between team affectivity and TMS. From a sample of 107 software implementation project teams, in a lagged field study, we find support for a mediated model in which high group NA, but not group PA, promotes environments psychologically unsafe for interpersonal risk‐taking (low PS) and which are negatively associated with TMS. This study extends prior research on the differential effects of PA and NA, by contributing to the limited research on group affectivity, environmental antecedents of TMS, and the mediating role of PS for predicting group level transactive processes and structures. Copyright © 2015 John Wiley & Sons, Ltd.